Penerapan Metode Card Sort Dalam Menyampaikan Materi Pelajaran PAI Q.S. Yunus: 40-41di Kelas XI SMAN 1 Geger Madiun - Sholichah, Mar'atus (Ngabari: Jurnal Studi Islam dan Sosial, 2020)
The initial objective of this study was to determine the steps for implementing the card sort method in delivering subject Q.S. Yunus: 40-41, and to find out the strengths and weaknesses of the card sort method. Experimental and observational approaches are used in this study. But finally found that the card sort method which is a learning strategy in the form of pieces of paper shaped like cards containing subject matter is quite fun to apply, more relaxed, and does not make students feel tense. The result is that students' memory of the subject matter is stronger. The steps for applying the card sort method are simple and uncomplicated so that this method is not only suitable for explicated in subject Q.S. Yunus: 40-41 only, but can also be applied to other subject matter, which requires the concentration of students to remember. Although the card sort method has weaknesses, if this method applied in delivering subject Q.S. Yunus: 40-41 makes students' knowledge equal because students not only get lessons from the teacher but also from their friends.